2020
DOI: 10.1007/s40256-020-00438-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Roles for Direct Factor Xa Inhibitors in Coronavirus Infections

Abstract: Human factor Xa (FXa) is a serine protease of the common coagulation pathway. FXa is known to activate prothrombin to thrombin, which eventually leads to the formation of cross-linked blood clots. While this process is important in maintaining hemostasis, excessive thrombin generation results in a host of thrombotic conditions. FXa has also been linked to inflammation via protease-activated receptors. Together, coagulopathy and inflammation have been implicated in the pathogenesis of viral infections, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 82 publications
1
38
0
Order By: Relevance
“…Patients with preexisting conditions, including pulmonary disease, cardiovascular disease and diabetes are at high risk of developing severe COVID-19 symptoms due to the higher baseline expression of FX in addition to other coagulation and inammatory mediators. 13,68 Based on these observations, inhibitors of FXa may have a potential role in the prophylaxis and treatment of COVID-19. This was explained by their ability to reduce cell infectivity, as well as reducing systemic inammation and coagulation.…”
Section: Fxa Inhibitory Activity Of the Isolated Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with preexisting conditions, including pulmonary disease, cardiovascular disease and diabetes are at high risk of developing severe COVID-19 symptoms due to the higher baseline expression of FX in addition to other coagulation and inammatory mediators. 13,68 Based on these observations, inhibitors of FXa may have a potential role in the prophylaxis and treatment of COVID-19. This was explained by their ability to reduce cell infectivity, as well as reducing systemic inammation and coagulation.…”
Section: Fxa Inhibitory Activity Of the Isolated Compoundsmentioning
confidence: 99%
“…Ten known avonoids (Fig. 1) were isolated and identied by comparing their 1 H, 13 C NMR spectra to those previously reported in literature (Tables S3, S4 and Fig. S2-S31; ESI †).…”
Section: Compounds Identicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that those FXa inhibitors can potentially block the viral entry of SARS-CoV-2 into the host by ceasing the fragmentation of spike protein into the S1 and S2 subunits. Thus, the concentration dependent inhibitors can obstruct the SARS-CoV-2 plaque formation in Vero E6 cells and thwart the entry of corona virus ( Al-Horani, 2020 ). Additionally, a few recent studies have suggested that FXa inhibitors can potentially inhibit TMPRSS2 and act against a wide spectrum of RNA and DNA viruses by ceasing the viral entry phase ( Du et al, 2007 ; Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a few recent studies have suggested that FXa inhibitors can potentially inhibit TMPRSS2 and act against a wide spectrum of RNA and DNA viruses by ceasing the viral entry phase ( Du et al, 2007 ; Kim et al, 2020 ). Therefore, FXa inhibitors can be a potential agent against COVID-19 attack ( Al-Horani, 2020 ). The anti-COVID-19 action of rivaroxaban is displayed in Figure 4 .…”
Section: Introductionmentioning
confidence: 99%